Beyond poverty alleviation: The impact of child support grants on healthcare access and contraception use in South Africa - Norman Tafirenyika Nhede; Adrino Mazenda; Dymon Gondwe (Dialogues in Health, 2025)
This study examines the impact of Child Support Grants (CSGs) on access to medical care and contraception use in South Africa, investigating whether social assistance can enhance healthcare access beyond its primary aim of alleviating poverty. While previous research highlights CSGs' poverty reduction and welfare enhancement effects, little is known about their effects on healthcare and reproductive healthcare access, especially given South Africa's healthcare disparities. Using data from the first wave of the 2020 National Income Dynamics Study—Coronavirus Rapid Mobile Survey (NIDS-CRAM), this study employs mediation analysis to analyse the effects of CSG receipt on healthcare and contraception access while controlling for socio-economic factors. The findings indicate a complex relationship. CSGs have a positive but insignificant indirect effect on healthcare and contraception access and a significant negative direct effect, suggesting that the current grant structure may not adequately address existing barriers. The results highlight the need for policy changes, indicating that while CSGs are vital as a social safety net, their effectiveness in improving healthcare access could be enhanced through increased grant amounts and targeted interventions to address healthcare costs and structural barriers.